2023
DOI: 10.1088/1367-2630/accdfb
|View full text |Cite
|
Sign up to set email alerts
|

Configurational dynamics of flexible filaments in bacterial active baths

Abstract: Biopolymers with microscale length and nanoscale cross-sections subjected to active forces is a common non-equilibrium phenomenon in living creatures. It is therefore crucial to intuitively present and investigate the detailed dynamics of such flexible filaments in an active bath full of living matter. Hence, by introducing fluorescent actin filament into an active suspension of motile bacteria at different number densities in a quasi-two-dimensional chamber, we directly visualize the detailed interaction proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Recently, there have been experimental studies focusing on the dynamics of anisotropic passive particles in active flows [62][63][64][65][66][67]. In comparison to Brownian motion scenarios, it has been observed that, in active flows, particles exhibit anomalous coupled diffusion behavior, specifically diffusing preferentially along their minor axis.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there have been experimental studies focusing on the dynamics of anisotropic passive particles in active flows [62][63][64][65][66][67]. In comparison to Brownian motion scenarios, it has been observed that, in active flows, particles exhibit anomalous coupled diffusion behavior, specifically diffusing preferentially along their minor axis.…”
Section: Introductionmentioning
confidence: 99%